1157. Optimal Isolation Periods Based on Time Interval to Elimination of Scabies After Topical Agent in the Real Clinical Practice. (26th November 2018) - Park, Jebyung; Park, Se Yoon; Han, Jaijun; Lee, So Young; Kim, Gil Eun; Jeong, Yeon Su; Kim, Jin Hwa; Lee, Eunyoung; Lee, Eun Jung; Yu, Shi Nae; Kim, Tark; Jeon, Min Hyok; et al.
Abstract: Background: Scabies reemerged globally as the ninth of most highly prevalent skin diseases from 1990 to 2010. Existing topical agents, like permethrine and lindane are highly effective showing 95% or more therapeutic response. Patient isolation is only recommended for one day after treating with topical agents. However, there is little evidence-based recommendation on optimal isolation period after treatment in healthcare settings to prevent secondary infection. Methods: All patients who were diagnosed from 2008 to 2017 with scabies at a referral university hospital in Seoul, Republic of Korea were analyzed. We investigated the time interval between symptom onset and diagnosis of scabies. The period from the application of topical agents and clinical resolution was also analyzed. Results: A total of 23 patients were diagnosed with scabies. There was no crusted scabies such as Norwegian scabies. Seventy percent of these patients were referred from long-term care facilities. Median number of treatment was three times per patient (Interquartile range [IQR], 2–3). Time interval between the onset of symptoms and the diagnosis of scabies was median 4 days (IQR, 2–14). Median isolation period was 13 days (IQR, 8–15). Dermatologist confirmed successful treatment of 16 patients, the median time until confirmation was 15 days (IQR, 8–17). Three patients discontinued isolation before dermatologist's confirmation. After re-evaluation by a dermatologist, one of the three was re-isolated due to persistent scabies infestation. Conclusion: Scabicides are highly efficacious, but repeated microscopic examination for confirming elimination is strongly recommended. Optimal isolation period should be individualized based on the repeated dermatologic examination. Disclosures: All authors: No reported disclosures.